Role of extracellular factors in axon regeneration in the CNS: implications for therapy. (November 2008) - Gervasi, Noreen M; Kwok, Jessica CF; Fawcett, James W
The glial scar that forms after an injury to the CNS contains molecules that are inhibitory to axon growth. Understanding of the mechanisms of inhibition has allowed the development of therapeutic strategies aimed at promoting axon regeneration. Promising results have been obtained in animal models, and some therapies are undergoing clinical trials. This offers great hope for achievement of functional recovery after CNS injury.